Translation and Tourism - Sulaiman, M. Zain. author. aut Link
XV, 223 p. 20 illus., 11 illus. in color.
Keywords: This book addresses one of the most central, yet criticised, solutions for international tourism promotion, namely translation. It brings together theory and practice, explores the various challenges involved in translating tourism promotional materials (TPMs), and puts forward a sustainable solution capable of achieving maximum impact in the industry and society. The solution, in the form of a Cultural-Conceptual Translation (CCT) model, identifies effective translation strategies and offers a platform for making TPM translation more streamlined, efficient and easily communicated. Using the English-Malay language combination as a case study, the book analyses tourism discourse and includes a road test of the CCT model on actual end-users of TPMs as well as tourism marketers in the industry. Guidelines for best practices in the industry round out the book, which offers valuable insights not only for researchers but also, and more importantly, various stakeholders in the translation, tourism and advertising industries.